Search for squark production in events with jets, hadronically decaying tau leptons and missing transverse energy at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (Elsevier B.V., 2009)
A search for supersymmetric partners of quarks is performed in the topology of multijet events accompanied by at least one tau lepton decaying hadronically and large missing transverse energy. Approximately 1 fb(-1) of p (p) over bar collision data from the Fermilab Tevatron Collider at a center of mass energy of 1.96 TeV recorded by the D detector is analyzed. Results are combined with the previously published do inclusive search for squarks and gluinos. No evidence of physics beyond the Standard Model is found and lower limits on the squark mass up to 410 GeV are derived in the framework of minimal supergravity with tan beta = 15, A(0) = -2m(0) and mu < 0, in the region where decays to tau leptons dominate. Gaugino masses m(1/2) are excluded up to 172 GeV. (C) 2009 Elsevier B.V. All rights reserved.